Deposits of disease-associated alpha-synuclein may be present in the dura mater in Lewy body disorders: implications for potential inadvertent transmission by surgery - Gelpi, Ellen; Visanji, Naomi P.; Hönigschnabl, Selma; Reiner, Angelika; Fischer, Peter; Lang, Anthony; Budka, Herbert; Kovacs, Gabor G. (Free Neuropathology, 2020)
Deposition of alpha-synuclein in the brain is a hallmark of Lewy body disorders. Alpha-synuclein has been considered to show prion-like properties. Prion diseases can be transmitted by the transplantation of cadaveric dura mater causing iatrogenic Creutzfeldt-Jakob disease. Recent observations of amyloid-β deposition in dural grafts support the seeding properties of amyloid-β. Here we assessed the presence of alpha-synuclein in dura mater samples as a potential transmissible seed source. We immunostained 32 postmortem dura mater samples; 16 cases with Lewy-body disorder (LBD) showing different pathology stages and 16 non-LBD cases for phosphorylated (Ser129) and disease-associated (5G4) alpha-synuclein. Disease-associated alpha-synuclein aggregates were identified in intradural nerve fibres and associated with a vessel in a single LBD-Braak stage 4 case. We conclude that alpha-synuclein is detectable, although rarely, in dura mater samples in patients with LBD. The risk of potential transmissibility of dural alpha-synuclein deserves assessment by complementary experimental studies.